2020
DOI: 10.1371/journal.pone.0244680
|View full text |Cite
|
Sign up to set email alerts
|

Multi-strain probiotics (Hexbio) containing MCP BCMC strains improved constipation and gut motility in Parkinson’s disease: A randomised controlled trial

Abstract: Objective We determined the effectiveness of a multi-strain probiotic (Hexbio®) containing microbial cell preparation MCP®BCMC® on constipation symptoms and gut motility in PD patients with constipation. Methods PD patients with constipation (ROME III criteria) were randomized to receive a multi-strain probiotic (Lactobacillus sp and Bifidobacterium sp at 30 X 109 CFU) with fructo-oligosaccaride or placebo (fermented milk) twice daily for 8 weeks. Primary outcomes were changes in the presence of constipation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 33 publications
(56 reference statements)
1
93
1
2
Order By: Relevance
“…Elaheh Amirani et al95% CI: -0.06 to 1.18) (Krüger, Hillesheim & Pereira, 2020). The MDA-UPDRS and NMSS were improved after usage of probiotics(Ibrahim et al, 2020). In chronic phase of PD, it is possible that cognition and brain functions are associated.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Elaheh Amirani et al95% CI: -0.06 to 1.18) (Krüger, Hillesheim & Pereira, 2020). The MDA-UPDRS and NMSS were improved after usage of probiotics(Ibrahim et al, 2020). In chronic phase of PD, it is possible that cognition and brain functions are associated.…”
mentioning
confidence: 86%
“…Ibrahim et al reported increased bowel opening frequency (BOF) and gut transit time (GTT)decreased in Parkinson's patients after 8 weeks usage of Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus lactis, Bifidobacterium infantis, Bifidobacterium longum(Ibrahim et al, 2020).In addition, following 4 weeks of using fermented milk containing several probiotic strains and prebiotic fiber, Barichella et al showed an increase in complete bowel movement (CBM)(Barichella et al, 2016). After 4 weeks of using a probiotic pill containing 10 billion CFU of eight different commercially available bacterial strains (Lactobacillus reuteri, Lactobacillus acidophilus, Lactobacillus gasseri, Bifidobacterium bifidum, Lactobacillus rhamnosus, Bifidobacterium longum, Enterococcus faecium, Enterococcus faecalis), spontaneous bowel movements (SBM) increased.…”
mentioning
confidence: 99%
“…and Bifidobacterium spp. have improved gut movement and ameliorated constipation in Parkinson’s disease patients [ 69 ]. Additionally, meta-analysis research on 2327 topics related to the influence of probiotics on chronic constipation in individuals revealed that oral intake of probiotics, particularly multi-strain probiotics, can primarily shorten gut transit time and increase fecal regularity [ 70 ].…”
Section: Probiotics and Gastrointestinal Dysfunctionsmentioning
confidence: 99%
“…This also supposes that the constipation often present in PD is caused by GI dysbiosis. To compliment this proposition, treatment with probiotics to repopulate the GI flora has successfully been implemented to alleviate PD-associated constipation [96][97][98]. Fecal microbiota transplantation (FMT) has likewise been used to treat constipation, with the first case report finding increased gastric motility and decreased leg tremors following FMT transplant through transendoscopic enteral tubing [99].…”
Section: Nascent Therapies For Pd Related Gi Dysfunctionmentioning
confidence: 99%